Penyelesaian Kredit Macet Dalam Hal Terjadinya Wanprestasi di Lembaga Perkreditan Desa (LPD) Desa Adat Tabola Sidemen - Cok Istri Wulan Pemayun; I Nyoman Sukandia; I Made Aditya Mantara Putra (Jurnal Analogi Hukum, 2024)
LPD is an economic institution owned by a traditional village that aims to help improve the standard of living of the village krama, supporting the development of the traditional village by providing credit facilities. A letter of agreement is required that binds the parties in granting credit. However, in practice, there are still problems of non-performance of obligations by customers, especially in the LPD of Tabola Sidemen Traditional Village. In connection with this, the problem is formulated, namely: 1. What are the factors that cause defaults in credit agreements at LPD Desa Adat Tabola Sidemen; 2. How are efforts to resolve bad credit in the event of default at LPD Desa Adat Tabola Sidemen? The research method used is the type of empirical legal research with the type of regulatory approach and sociological approach or facts. The results show that the factors that cause default are internal factors and external factors. Internal factors from the LPD and external factors caused by customers. Efforts to resolve bad credit for defaults are carried out by credit restructuring, litigation and non-litigation efforts.